ひきざん Flashcards
13 - 1 =
12
17 - 2 =
15
12 - 9
3
12 - 9 =
( 10 + 2) - 9 =
( 10 - 9 ) + 2 =
1 + 2
14 - 6
8
14 - 6 =
( 10 + 4 ) - 6 =
( 10 - 6 ) + 4 =
4 + 4 =
15 - 8 =
7
15 - 8 =
( 10 + 5 ) - 8 =
( 10 - 8 ) + 5 =
2 + 5 =
18 - 8 =
10
12 - 6 =
6
12 - 6 =
( 10 + 2 ) - 6 =
( 10 - 6 ) + 2 =
4 + 2 =
14 - 1 =
13
19 - 3 =
16
15 - 2 =
13
17 - 9 =
8
17 - 9 =
( 10 + 7 ) - 9 =
(10 - 9 ) + 7 =
1 + 7
11 - 6 =
5
11 - 6 =
( 10 + 1 ) - 6 =
( 10 - 6 ) + 1 =
4 + 1 =
16 - 1 =
15
15 - 4 =
11
11 - 3 =
8
11 - 3 =
( 10 + 1 ) - 3 =
( 10 - 3) + 1 =
7 + 1 =
18 - 2 =
16
15 - 3 =
12
11 - 1 =
10
13 - 6 =
7
13 - 6 =
( 10 + 3 ) - 6 =
( 10 - 6 ) + 3 =
4 + 3 =
19 - 7 =
12
14 - 3
11
18 - 7 =
11
17 - 7 =
10
13 - 5 =
8
13 - 5 =
( 10 + 3 ) - 5 =
( 10 - 5 ) + 3 =
5 + 3 =
18 - 3 =
15
17 - 8 =
9
17 - 8 =
( 10 + 7 ) - 8 =
( 10 - 8 ) + 7 =
2 + 7
13 - 4 =
9
13 - 9 =
( 10 + 3 ) - 9 =
( 10 - 9 ) + 3 =
1 +3
13 - 3 =
10
11 - 5 =
6
11 - 5 =
( 10 + 1 ) - 5 =
( 10 - 5) + 1 =
5 + 1 =
11 - 8 =
3
11 - 8 =
( 10 + 1 ) - 8 =
( 10 - 8 ) + 1 =
2 + 1 =
16 - 6 =
10
16 - 7 =
9
16 - 7 =
( 10 + 6 ) - 7 =
(10 - 7 ) + 6 =
3 + 6 =